The limitations of testicular organoids: are they truly as promising as we believe? - Mecca, R; Tang, S; Coward, K; Jones, C (CSIRO Publishing, 2024)
Organoid systems have revolutionised various facets of biological research by offering a three-dimensional (3D), physiologically relevant in vitro model to study complex organ systems. Over recent years, testicular organoids have been publicised as promising platforms for reproductive studies, disease modelling, drug screening, and fertility preservation. However, the full potential of these systems has yet to be realised due to inherent limitations. This paper offers a comprehensive analysis of the current challenges associated with testicular organoid models. Firstly, we address the inability of current organoid systems to fully replicate the intricate spatial organisation and cellular diversity of the in vivo testis. Secondly, we scrutinise the fidelity of germ cell maturation within the organoids, highlighting incomplete spermatogenesis and epigenetic inconsistencies. Thirdly, we consider the technical challenges faced during organoid culture, including nutrient diffusion limits, lack of vasculature, and the need for specialised growth factors. Finally, we discuss the ethical considerations surrounding the use of organoids for human reproduction research. Addressing these limitations in combination with integrating complementary approaches, will be essential if we are to advance our understanding of testicular biology and develop novel strategies for addressing reproductive health issues in males.